Novas práticas de acesso e compartilhamento da informação: um estudo sobre as Bibliotecas Parque - SILVA, Hanna Katlen Martins (2017)
The Park Libraries are increasingly consolidated as a new vision of public library that offers services that go far beyond loan and consultation to the bibliographic collection. Park Libraries are multifunctional libraries that, through cultural actions and reading encouragement, contribute to the social inclusion of citizens with lower purchasing power, who are often far from public policies. The implantation of a Park Library in a socioeconomically disadvantaged community generates significant transformations in society, through the Park Libraries these citizens have access to information, education and culture. The interaction between Librarian and social mediator is a determinant factor for the good functioning of the Park Libraries, as well as the participation of the population in the programming of the library, the objective of this study is to show what are the new practices of access and sharing of the information executed by Libraries Park , And how this institution has become an important tool for the social and cultural development of the communities to which it is inserted.